2001
DOI: 10.1080/13691060110045995
|View full text |Cite
|
Sign up to set email alerts
|

Can venture capital-backed IPOs compete with seasoned public companies?

Abstract: This paper investigates whether a small group of venture capital-backed initial public offerings (IPOs) were able to compete effectively with seasoned competitors. Previous studies have shown that IPOs have generally under performed seasoned companies. Using data from the Venture Capital Journal and Compustat, this paper tests for statistically significant differences in the long run market and operating performances of a carefully matched set of IPOs and seasoned companies. Using Wilcoxon paired sample tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…If a company goes public prematurely at the insistence of venture capitalists due to their self interest, the effects can be detrimental (Gompers, 1996;Loughran and Ritter, 2004). As a result, in accordance with these theoretical predictions, empirical studies have sometimes shown that VC-backed companies that have undertaken an IPO have higher profitability (Beatty and Zajac, 1994;Rindermann, 2003;Williams et al, 2005), higher growth (Belden et al, 2001;Florin, 2005) or better stock market performance (Jane and Kini, 1995;Bradley and Jordan, 2002;Arthurs et al, 2009). Others have demonstrated that VC-backed IPO firms are not significantly different from non-VC-backed IPO firms (Rosa et al, 2003;Jelic et al, 2005;Campbell and Frye, 2006;Elston and Yang, 2010), and some have even found a negative impact of VC on funded companies ' performance (Megginson and Weiss, 1991;Ritter, 1991;Lee and Wahal, 2004;Bruton et al, 2009).…”
mentioning
confidence: 58%
“…If a company goes public prematurely at the insistence of venture capitalists due to their self interest, the effects can be detrimental (Gompers, 1996;Loughran and Ritter, 2004). As a result, in accordance with these theoretical predictions, empirical studies have sometimes shown that VC-backed companies that have undertaken an IPO have higher profitability (Beatty and Zajac, 1994;Rindermann, 2003;Williams et al, 2005), higher growth (Belden et al, 2001;Florin, 2005) or better stock market performance (Jane and Kini, 1995;Bradley and Jordan, 2002;Arthurs et al, 2009). Others have demonstrated that VC-backed IPO firms are not significantly different from non-VC-backed IPO firms (Rosa et al, 2003;Jelic et al, 2005;Campbell and Frye, 2006;Elston and Yang, 2010), and some have even found a negative impact of VC on funded companies ' performance (Megginson and Weiss, 1991;Ritter, 1991;Lee and Wahal, 2004;Bruton et al, 2009).…”
mentioning
confidence: 58%
“…Gompers and Lerner 1998), the role of venture capitalists in the decision of the firm to go public and the performance of venture capital backed initial public offerings (e.g. Barry et al 1990, Megginson and Weiss 1991, Brav and Gompers 1997, Espenlaub et al 1999, Belden et al 2001, the ability of venture capitalists to make timely and profitable exits (e.g. Cumming and MacIntosh 2001), and venture capital risk-return profiles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wright, Gilligan and Amess, 2009). These studies range from macro-economic panel estimations (e.g., Romain and van Pottelsberghe, 2004), to estimations mainly based on sectoral data (e.g., Kortum und Lerner, 2000;Tykvová, 2000;Hirukawa and Ueda, 2008a,b) as well as to micro-econometric analyses and paired sample tests (e.g., Hellmann andPuri, 2000, 2002;Belden, Keeley and Knapp, 2001;Botazzi and Da Rin, 2002;Engel, 2003;Engel and Keilbach, 2007;Sorensen, 2007;Lerner, Sorensen and Stromberg, 2008;Bloom, Sadun and van Reenen, 2009). This paper is part of the latter strand, which contrasts the development of individual firms backed by venture capital with a hypothetical 'counterfactual' observation based on the careful selection of a comparable control group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Figure 1B the boundary of financially feasible projects with a given Var(π) therefore moves upward and away from the diagonal by the distance m. In this situation a financing gap arises, as certain projects are no longer considered financially feasible due to increased monitoring, advising, and control costs. We also assume that m grows progressively with uncertainty, , 1991, 2001Kannianen and Keuschnigg, 2004;Keuschnigg and Nielsen, 2004). As a result of their diligent project screening and monitoring, as well as their accompanying advisory services, they shift the boundary of financially feasible projects outward, thereby creating a new segment in the corporate finance market ( Figure 1C).…”
Section: The Specific Financing Functionmentioning
confidence: 99%